Reversing poverty trends in Africa: case of Nigeria and others countries - Oladipo, Funke (Corpus Intellectual, 2023)
Extreme poverty is a major issue in many Africa, it’s crucial that we address it right now since it negatively impacts people’s lives. These issues include not having access to enough food, a safe place to live, clean water to drink, adequate reading and writing skills, the death of many babies and mothers, a large number of people lacking jobs, and a sense of weakness and helplessness. In order for the poor to earn more money and obtain more employment, the economy must be strengthened, this will help to reduce poverty. This can be accomplished by altering current procedures to better utilize resources. Additionally, it entails seeing to the fundamental requirements of the impoverished. Giving small loans to folks who wish to launch enterprises is another way we can assist. We must ensure that, there are effective channels for selling what individuals produce and create incentives for corporations to lend a hand. Finally, by providing grants, social safety nets and money directly to those in need, we can guarantee that they receive it.